75 Paediatric Cannabinoid Hyperemesis Syndrome in the Emergency Department: a 5-year Retrospective Review. (19th August 2020) - Foster, Daniel; Van Aarsen, Kristine; Yan, Justin; Teefy, John; Lynch, Tim
Abstract: Background: Cannabinoid Hyperemesis Syndrome (CHS) in paediatric patients is poorly characterized. Identification and treatment of adolescents presenting to the emergency department (ED) for suspected CHS is challenging. Given the paucity of literature on paediatric CHS and the recent legalization of cannabis, it is important to gain a better understanding of this disorder. Objectives: The objective of this study was to describe demographics and ED visit data of paediatric patients presenting to the ED with suspected CHS. Design/Methods: A retrospective chart review was conducted of paediatric patients (12-17 years) with suspected CHS presenting to one of two tertiary-care EDs; one paediatric (annual census 38, 500) and one paediatric and adult (annual census 60, 000) between April 2014-March 2019. Charts were selected based on discharge diagnosis of abdominal pain or nausea/vomiting with positive cannabis urine screen, or discharge diagnosis of cannabis use, using ICD-10 codes. Patients with confirmed or likely diagnosis of CHS were identified and data including demographics, clinical history, and ED investigations/treatments were recorded by a trained research assistant. Results: A total of 242 patients met criteria for review. Thirty-nine were identified as having a confirmed or likely diagnosis of CHS (mean age 16.2, SD 0.85 years with 64% female), 87% were triaged as either CTAS-2 or CTAS-3 and 80% of patients had cannabis use frequency/duration documented. Of these, 89% reported at least daily use, the mean consumption was 1.30g/day (SD 1.13g/day), and all reported ≥6 months of heavy use. Sixty-nine percent of patients had at least one psychiatric comorbidity. When presenting to the ED, all had vomiting, 81% had nausea, 81% had abdominal pain and 30% reported weight loss. Investigations done included venous blood gas (30%), pregnancy test in females (84%), liver enzymes (57%), pelvic or abdominal ultrasound (19%), abdominal X-ray (19%), and CT head (5%). Eighty-nine percent of patients received treatment in the ED with 81% receiving anti-emetics, 68% receiving intravenous fluids, and 22% receiving analgesics. Normal saline was the most used intravenous fluid (80%) and ondansetron was the most used anti-emetic (90%). Cannabis was suspected to account for symptoms in 74% (with 31% of these given the formal diagnosis of CHS). Sixty-two percent of patients had another visit to the ED within 30 days (59% of these for similar symptoms). Conclusion: This study of paediatric CHS reveals unique findings including a preponderance of female patients, a majority that consume cannabis daily, and weight loss reported in nearly 1/3rd. Many received extensive workups and most had multiple clustered visits to the ED.